Developing a Strategy for COVID-19 Control Among Hard-to-Reach Migrant Communities: The Experience of Roma 2 Local Health Authority - Rosso, Annalisa; Rinaldi, Alessandro; Coluzzi, Daniele; Perrelli, Fabrizio; Napoli, Pier Angela; Flacco, Maria Elena; Manzoli, Lamberto; De Angelis, Giuseppe (International Journal of Public Health, 2023)
Roma 2 Local Health Authority (ASL) developed a strategy to control the COVID-19 epidemic in Hard-to-reach (HTR) migrant communities, addressing both the containment of clusters in informal settlements and access to COVID-19 vaccination. The strategy was based on a strong collaboration of different services across the ASL and with Non-Governmental Organizations (NGOs). NGOs were involved in the active surveillance, reporting of COVID-19 suspected cases to the ASL and information to the communities. Health interventions (eg. COVID-19 tests, contact tracing, vaccination) were offered in outreach in HTR communities' life places. From April 2020 to February 2021, 15 outbreaks were controlled, for a total of over 4,500 persons reached, and 265 COVID-19 cases identified. From July to November 2021, vaccinations were offered in outreach or with dedicated sessions, reaching 1,398 people. This intervention model may lay the foundations for the design of public health strategies, not only aimed at HTR populations.